2008
DOI: 10.1158/1078-0432.ccr-07-1032
|View full text |Cite
|
Sign up to set email alerts
|

Serum Interleukin-6 Level but not Genotype Predicts Survival after Resection in Stages II and III Gastric Carcinoma

Abstract: Purpose: It has been suggested that interleukin-6 (IL-6) is a prognostic indicator for survival in patients with gastric carcinoma, but this has not been proved using survival analysis. In Asians, the -634G allele is associated with increased IL-6 production. The objective of this study was to evaluate the association between serum IL-6 levels, -634G/C polymorphism, and overall survival after resection for gastric carcinoma. Experimental Design: A total of 155 consecutive patients with gastric carcinoma were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
77
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 43 publications
2
77
0
Order By: Relevance
“…By inducing cytokines including IL6 and IL8, H. pylori plays important roles in gastric cancer development (4), including tumor initiation (5), promotion (6), and metastasis (7). IL6 that activates STAT3 has particularly important roles in the malignant transformation of gastric and intestinal epithelial cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…By inducing cytokines including IL6 and IL8, H. pylori plays important roles in gastric cancer development (4), including tumor initiation (5), promotion (6), and metastasis (7). IL6 that activates STAT3 has particularly important roles in the malignant transformation of gastric and intestinal epithelial cells (8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that -634G/C polymorphism is associated with the clinical outcome of breast, gastric, prostate and ovarian cancers (33)(34)(35)(36). One study investigated the association between VEGF polymorphism and the prognosis of osteosarcoma, but this previous study did not identify that the -634G/C polymorphism played a role in the clinical outcome of osteosarcoma (37).…”
Section: Discussionmentioning
confidence: 98%
“…Various clinical studies have correlated high pretreatment serum IL6 level with poor outcome in patients with different types of cancer including head and neck squamous cell carcinoma (28), stage II and III gastric carcinoma (29), prostate cancer (30), metastatic renal cell carcinoma (31), metastatic breast cancer (32), and ovarian cancer (33). Elevated levels of IL6 in cancer patients could be due to increased expression in normal immune cells as a consequence of chronic (systemic) inflammation, and/or from stromal or cancer cells within tumors.…”
Section: Discussionmentioning
confidence: 99%